CADRES OF THE INTEGRATED HEALTH POST FOR ELDERLY AND THEIR SATISFACTION: HERZBERG THEORY APPROACH - Nabila Ramadhania; Sharon Gondodiputro; Merry Wijaya; Didah Didah; Ariyati Mandiri (Sosiohumaniora, 2020)
Integrated health post (posbindu) is a place for the elderly to obtain various health services to improve their quality of life.  The satisfaction of the health care volunteers (cadres) has an important role in the success of the posbindu. The higher the cadre’s satisfaction, the higher the performance in managing the posbindu. According to Herzberg, two factors that contributed to the work satisfaction, namely motivator factor and hygiene factor. Identifying these factors is important, so that cadres can remain active and satisfy in doing their work in the posbindu. The purpose of this study was to explore the components of cadres’ satisfaction in providing health services in the posbindu based on Herzberg’s factors A qualitative phenomenological study was conducted on 12 active and 6 inactive cadres in 16 posbindu, Bandung City, West Java, Indonesia. A purposive sampling was performed to select the posbindu and the cadres. Data collection was carried out by an in-depth interview to explore the work satisfaction factors based on the concept of the Herzberg theory. Triangulation was based on the result of active and inactive cadres interviews, as well as observation of the activities during the posbindu. This study discovered practicing religious teachings and social relations as two new components that can influence satisfaction in the workplace.